Game of thorns : the inside story of Hillary Clinton's failed campaign and Donald Trump's winning strategy - Wead, Doug (New York : Center Street, 2017)
An examination of the campaign strategies of the 2016 presidential election describes how Donald Trump's abrasive tactics struck a chord with previously unaligned segments of the country, undermining Clinton's traditional campaign efforts.
Includes bibliographical references (pages 379-403).
Keywords: Clinton, Hillary Rodham; Trump, Donald, -- 1946-; Presidents -- United States -- Election -- 2016.; Political culture -- United States; United States -- Politics and government -- 2009-